1976
DOI: 10.1016/s0010-9452(76)80042-1
|View full text |Cite
|
Sign up to set email alerts
|

Aphasic Disorders in Matching Tasks Involving Conceptual Analysis and Covert Naming

Abstract: Aphasic, non-aphasic brain-damaged, schizophrenic and normal Ss were required to select which of two pictures in each item was indicated by a third picture. The latter was related to the referent not through direct associations but only through a mediator: a homonym -- the name for clue and referent --, a situational association, or a perceptual feature common to both. The availability of these mediators was to be tested. Aphasics were as good as normals when the task could be solved via situational associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…It was beyond the scope of this study to investigate and address the question of a distinction between impaired semantic representations and impaired semantic access mechanisms that has been discussed extensively for PWA, e.g., [39,80,81]. For an overview of this discussion and a study that may disprove some of the accounts of the impaired access theories compare Chapman, et al [82]. Additionally, and partly related to the aforementioned aspect, the impact of neuropsychological disorders that can accompany aphasia, like executive disfunctions or visuo-constructive disorders, have not been addressed.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…It was beyond the scope of this study to investigate and address the question of a distinction between impaired semantic representations and impaired semantic access mechanisms that has been discussed extensively for PWA, e.g., [39,80,81]. For an overview of this discussion and a study that may disprove some of the accounts of the impaired access theories compare Chapman, et al [82]. Additionally, and partly related to the aforementioned aspect, the impact of neuropsychological disorders that can accompany aphasia, like executive disfunctions or visuo-constructive disorders, have not been addressed.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…The BOSU has not yet been administered to people with right brain damage but there is a long tradition of tests of similar format that compare matching of pictures or other meaningful stimuli based on selected semantic features to matching by global similarity. They regularly found that matching according to selected features is defective only in people with left brain damage (Cohen & Kelter, 1979;De Renzi, Scotti, & Spinnler, 1969;Hartmann, Goldenberg, Daumüller, & Hermsdörfer, 2005;Kelter, Cohen, Engel, List, & Strohner, 1976;Vignolo, 1990). Of course, the leading symptom of left brain damage is aphasia and both, defective pantomime and defective matching by selected semantic features are regularly accompanied by aphasia.…”
Section: Predictors Of Comprehensibility Of Gesturesmentioning
confidence: 99%
“…However, there are reasons to investigate the intact status of the types of knowledge that might be presumed responsible for his good performance. The work of the Konstanz group Kelter et al, 1976, Cohen, Kelter & Woll, 1980review in Vignolo, 1999) distinguishes between types of categorisation tasks. Their tasks, similar in design to those used in the Pyramids and Palm Trees Test (Howard & Patterson, 1992), ask the patient to decide which two out of three pictures go together.…”
Section: Stimulimentioning
confidence: 99%